High energy storage efficiency of NBT-SBT lead-free ferroelectric ceramics. Issue 16 (15th August 2022) - Zhou, Xinyi; Liu, Kai; Yan, Zilin; Xie, Bing; Fan, Pengyuan; Chen, Sheng-Gui; Samart, Chanatip; Salamon, David; Tan, Hua; Fan, Zhongming; Zhang, Haibo
Abstract: Ceramic-based dielectrics have been widely used in pulsed power capacitors owing to their good mechanical and thermal properties. Bi0.5 Na0.5 TiO3 -based (NBT-based) solid solutions exhibit relatively high polarization, which is considered as a promising dielectric energy storage material. However, the high remnant polarization and low energy efficiency limit their application in dielectric capacitors. Herein, a typical relaxor ferroelectric Sr0·7 Bi0·2 TiO3 (SBT) was introduced into the NBT system to strengthen the overall relaxor behavior, resulting in reduced remnant polarization. We prepared (1- x )NBT- x SBT ( x = 0.35, 0.45, 0.55, and 0.65) ceramics by the conventional solid-phase reaction method and further investigated their microstructures, dielectric and energy storage properties. With the increase of SBT content, the size of the grains and the maximum dielectric constant gradually decreased, simultaneously. Furthermore, the dielectric shoulder corresponding to the maximum dielectric constant shifted to a lower temperature, indicating that the enhancement of polarization dynamics was a consequence of the domain refinement. As a result, the optimum property was identified in the 0.45NBT-0.55SBT sample with a high recoverable energy density of 1.34 J/cm 3 and an outstanding energy efficiency of 96% at a low electric field of 100 kV/cm.